Effect of CO2 Laser on the Prevention of White Spot Lesions During Fixed Orthodontic Treatment: A Randomized Clinical Trial - Majid Mahmoudzadeh; Sara Alijani; Loghman Rezaei Soufi; Maryam Farhadian; Fatemeh Namdar; Somayeh Karami (Galenos Yayinevi, 2019)
Objective:This study aimed to assess the effect of carbon dioxide (CO2) laser on prevention of white spot lesions (WSLs) associated with fixed orthodontic treatment.Methods:In this parallel controlled trial, 554 maxillary anterior teeth in 95 patients with age range of 12-30 years were included. The samples were randomly divided in two groups: 1) CO2 laser (n=278) and 2) control (n=276) groups. Following bracket attachment, the teeth in the laser group were exposed to CO2 laser (0.4 mw, 10.6 μm, 5 Hz) for 20 s, and the control group received placebo light. Incidence, severity, and extent of the lesions were assessed in four surface regions (gingival, incisal, mesial, and distal) at baseline and 6 months post-irradiation. The inter-group comparison was performed by the Mann-Whitney U test and McNemar analysis.Results:A significant difference regarding WSLs incidence in all teeth was observed between the two study groups (p<0.001). The two study groups illustrated a significant difference in lesion extent and incidence in incisal, mesial, and distal regions (p<0.05). The WSLs were significantly different in terms of severity in the incisal and mesial sites (p<0.05).Conclusion:The CO2 laser irradiation seemed to effectively prevent incidence of WSLs. In addition, its effectiveness varied depending on the surface region.